Night of remembrance - Yusuf Islam; Mountain of Light Production; EMI (Malaysia) Sdn. Bhd. ([S.l.] : Mountain of Light Production, 2004)
Night of rememberance commemorated 20 years of Islamia schools. Held at the Royal Albert Hall on 20th October 2003, Yusuf Islam was joined by friends from around the world to celebrate this anniversary and share the universal message of peace
cd 1. The songs cd 2. The talks
Title from container
Singer: Yusuf Islam
Keywords: Music -- Religious aspects -- Islam; Songs, English; Music